Fixed-point iteration processes for non-Lipschitzian mappings of asymptotically quasi-nonexpansive type. (10th June 2003) - Sahu, Daya Ram; Jung, Jong Soo
Abstract : We study convergences of Mann and Ishikawa iteration processes for mappings of asymptotically quasi-nonexpansive type in Banach spaces.